Model Kolaborasi Bidan dan Terapis Akupunktur dalam Penerapan Manajemen Komplementer Masa Nifas - Prihatono, Amal; Prisusanti, Retno Dewi (Jurnal Ilmiah Kedokteran dan Kesehatan, 2026)
Background: The postpartum period is a critical stage for maternal recovery, characterized by physical and emotional adjustments. Conventional midwifery care often lacks complementary interventions that can enhance maternal well-being. Collaboration between midwives and acupuncture therapists is expected to create a more holistic, evidence-based complementary care model for postpartum mothers. Methods: This study employed a mixed-methods sequential exploratory design. The qualitative phase involved in-depth interviews with 12 midwives, 6 acupuncture therapists, and 10 postpartum mothers to identify needs, barriers, and perceptions toward collaborative care. The quantitative phase involved 30 postpartum mothers who received a 14-day collaborative intervention combining midwifery care and acupressure therapy. Data were analyzed using paired t-tests with a significance level of p<0.05. Results: Significant improvements were observed after implementing the collaborative model: pain scores decreased from 5.8 ± 1.2 to 3.1 ± 0.9 (p=0.001), anxiety scores reduced from 16.5 ± 4.3 to 10.2 ± 3.1 (p=0.001), and breast milk production increased from 410 ± 80 ml to 560 ± 90 ml (p=0.002). Sleep quality improved from 8.2 ± 2.1 to 5.0 ± 1.6 (p=0.003), and maternal satisfaction rose from 3.6 ± 0.7 to 4.7 ± 0.4 (p=0.001). Discussion: The collaborative midwife–acupuncturist model effectively accelerated postpartum recovery through acupressure stimulation and holistic emotional support. This aligns with the World Health Organization’s (2021) Framework for Interprofessional Collaborative Practice, emphasizing integrated, patient-centered care. Conclusion: The collaborative model between midwives and acupuncture therapists effectively enhances the physical and psychological well-being of postpartum mothers. It is feasible for implementation in midwifery services as an evidence-based complementary care approach.